Bacterial Contamination and Antimicrobial Resistance in Two-Spotted (Gryllus bimaculatus) and House (Acheta domesticus) Cricket Rearing and Harvesting Processes - J. Mitchaothai; Nils Th. Grabowski; Rachakris Lertpatarakomol; Tassanee Trairatapiwan; Achara Lukkananukool (Veterinary Sciences, 2024)
mainly involved penicillin G, amoxicillin, ampicillin, erythromycin, lincomycin, and tiamulin. Thus, good farm management with proper sanitation practices (such as cleaning and keeping the environment dry), as well as boiling crickets during the harvesting process, may help ensure the safety of edible cricket production.
Keywords: Insect Utilization and Effects; Insect and Pesticide Research; Insects and Parasite Interactions